Digital economy and international taxation : the digital revolution and its impact on the discourse of international tax law - Campos, Marcio Augusto Pereira da Silva (2021)
Tese (doutorado)—Universidade de Brasília, Faculdade de Direito, Programa de Pós-Graduação em Direito, 2021.